Flame retardants for epoxy resins: Application‐related challenges and solutions. Issue 1 (8th January 2022) - Kandola, Baljinder K.; Magnoni, Federico; Ebdon, John R.
Abstract: Owing to their high versatility from chemical and processing perspectives and hence their capability of being tailored for required properties, epoxy resins are used in a wide range of applications ranging from general use to high performing materials. Most of the applications though also require conformation to certain specified fire safety regulations. The flammability (and other properties) of cured epoxy resins depend on the type of resin, curing agent and curing process used, which have been highlighted in this article. The focus of the review though is on the type of flame retardants required to achieve certain levels of flame retardancy. There are numerous research articles and reviews dealing with flame retardancy of epoxy resins in the open literature and it is beyond the scope of this review to cover them all, hence only selected representative papers are discussed here, while references to previous reviews are provided that cover additional work. Different flame retardants and their chemically modified/synthesized variants developed by various researchers have been critically reviewed in terms of their flame retardant efficiency relative to their commonly used/ commercially available counterparts. The issues related to their suitability in terms of processability and performance in certain applications have also been discussed.